Reactivity of Cationic Terminal Borylene Complexes: Novel Mechanisms for Insertion and Metathesis Chemistry Involving Strongly Lewis Acidic Ligand Systems - De, S; Pierce, G; Vidovic, D; Kays, D; Coombs, N; Jemmis, E; Aldridge, S (2009)
The reactions of terminal borylene complexes of the type [CpFe(CO) 2(BNR2)]+ (R = i1Pr, Cy) with heteroallenes have been investigated by quantum-chemical methods, in an attempt to explain the experimentally observed product distributions. Reaction with dicyclohexylcarbodiimide (CyNCNCy) gives a bis-insertion product, in which 1 equiv of carbodiimide is assimilated into each of the Fe=B and B=N double bonds to form a spirocyclic boronium system. In contrast, isocyanates (R'NCO, R' = Ph, 2,6XyI, Cy; XyI = CoH3Me2) react to give isonitrile complexes of the type [CpFe(CO)2(CNR')]+, via a net oxygen abstraction (or formal metathesis) process. Both carbodiimide and isocyanate substrates are shown to prefer initial attack at the Fe=B bond rather than the B=N bond of the borylene complex. Further mechanistic studies reveal that the carbodiimide reaction ultimately leads to the bis-insertion compounds [CpFe(CO)2C(NCy)2B(NCy)2CNR2] +, rather than to the isonitrile system [CpFe(CO)2(CNCy)] +, on the basis of both thermodynamic (product stability) and kinetic considerations (barrier heights). The mechanism of the initial carbodiimide insertion process is unusual in that it involves coordination of the substrate at the (borylene) ligand followed by migration of the metal fragment, rather than a more conventional process: i.e., coordination of the unsaturated substrate at the metal followed by ligand migration. In the case of isocyanate substrates, metathesis products are competitive with those from the insertion pathway. Direct, single-step metathesis reactivity to give products containing a coordinated isonitrile ligand (i.e. [CpFe(CO)2(CNRO]+) is facile if initial coordination of the isocyanate at boron occurs via the oxygen donor (which is kinetically favored); insertion chemistry is feasible when the isocyanate attacks initially via the nitrogen atom. However, even in the latter case, further reaction of the monoinsertion product so formed with excess isocyanate offers a number of facile (low energetic barrier) routes which also generate [CpFe(CO)2(CNRO]+, rather than the bis-insertion product [CpFe(CO)2C(NRO(O)B(NRO(O)CNR2]+ (i.e., the direct analogue of the observed products in the carbodiimide reaction). © 2009 American Chemical Society.